A molecular survey of bovine Theileria parasites among apparently healthy cattle and with a note on the distribution of ticks in eastern Turkey - Aktas, Munir; Altay, Kursat; Dumanli, Nazir (Elsevier, 2006)
A survey of Theileria parasites in cattle in eastern Turkey was carried out using specific polymerase chain reaction. A total of 252 blood samples were collected from clinically healthy cattle between June and July 2004. Of 252 blood samples examined, 41 (16%) were positive for piroplasms by microscopy, whereas 114 (45%) were positive for the presence of at least one species of Theileria by PCR. The percentages of positive animals for Theileria annulata and benign Theileria species (Theileria sergenti/buffeli/orientalis) were 39% (99/252) and 7% (18/252), respectively. By allele-specific PCR examination of 18 field isolates which were positive for benign Theileria parasites, 8 samples were only amplified by B-type specific primers and 10 samples were amplified by both of the B and C-type specific primers, indicating a mixed infection with B and C-type of the parasite. None of the field isolates was amplified by I-type specific primers. Three samples were co-infected with T. annulata and benign Theileria parasites. Two of them which were infected with B-type parasite were also infected with T. annulata, the other sample which was infected both of B and C-type parasites was also infected with T. annulata. A total of 724 ixodid ticks were collected from the cattle. Hyalomma anatolicum anatolicum was the dominant species with 32% (230/724) in the region. H. a. excavatcum. Boophylus annulatus and Rhipicephalus bursa represented 25% (183/724), 19% (140/724) and 15% (112/724) of the total number of ticks, respectively. R. sanguineus was the minor species and represented 8% (59/724) of the tick population. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cattle; microscopy; PCR; Theileria; tick